Pengembangan Materi Puisi melalui Audio Visual terhadap Kemampuan Menyimak Siswa: Penelitian - Yantisana Gulo; Imansudi Zega; Lestari Waruwu; Noibe Halawa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop audio-visual based poetry materials to improve the listening skills of grade VIII students of SMP Negeri 2 Lahewa Timur, using the Borg and Gall development model. The instruments used include material validation questionnaires, language, design, and student responses and test results. The validation results showed an increase in product quality, with revision II scores reaching above 90% from all experts. The materials proved to be very practical (84% practicality in small trials and 90% in large trials) and effective (learning completeness 100% and 90%). The audio-visual poetry materials developed proved to be feasible, practical, and effective in improving the listening skills of grade VIII students of SMP Negeri 2 Lahewa Timur.